The Process of the Creation and Development of the Romea Strata European Cultural Route in Poland as a Tool Supporting Local Entrepreneurship and Cross -Sector Collaboration - Zdon-Korzeniowska, Małgorzata; Mróz, Franciszek (Przedsiębiorczość - Edukacja, 2025)
The aim of this article is to present the process of creating the Romea Strata European Cultural Route in Poland as an instrument supporting local entrepreneurship and cross -sectoral cooperation. Romea Strata, the youngest European Cultural Route, runs from Tallinn to Rome and already plays a significant role in European tourism space. The analysis covers the route’s development proces from the conceptual phase, through signage and infrastructure development, to stakeholder engagement and management mechanisms. The research methods applied in the article include a literature review, focus group discussions, field observations, exploratory hikes and in -depth interviews with local community representatives and route coordinators. The collected data allowed for the identification of stages in developing the route as a tourism product and patterns of cross -sectoral collaboration. The results indicate that a well- designed and effectively managed cultural route can stimulate local entrepreneurship, strengthen community identity and support the preservation of cultural heritage. The Romea Strata exemplifies a tourism product that integrates educational, academic and entrepreneurial initiatives, demonstrating how the process of creating a heritage -based product can contribute to sustainable regional development.